New and rare coastal fishes in the Azores islands: occasional events or tropicalization process?. Issue 2 (10th July 2013) - Afonso, P.; Porteiro, F. M.; Fontes, J.; Tempera, F.; Morato, T.; Cardigos, F.; Santos, R. S.
Abstract : Seven coastal fish species are newly reported for the remote north Atlantic archipelago of the Azores: Mediterranean sand eel Gymnammodytes cicerelus, bar jack Caranx ruber, two‐banded seabream Diplodus vulgaris, bastard grunt Pomadasys incisus, unicorn leatherjacket filefish Aluterus scriptus and longspined porcupinefish Diodon holacanthus . The occurrence is also confirmed for 19 species that had been hitherto cited occasionally for the region, totalling a list of two elasmobranchs and 23 teleosts. Diplodus vulgaris, which appears to have recently colonized the islands, as well as roughtail stingray Dasyatis centroura and golden grey mullet Liza aurata, re‐cited based on new records, are frequent or common coastal species in the Azores. The remaining 22 species, exceptional or rare in the region, are of tropical or subtropical affinity and find their northernmost distribution limit within the central and north‐east Atlantic Ocean precisely in the Azores. This biogeographical pattern contrasts with that of the Azorean coastal fish community and suggests a tropicalization process in the region in line with previous findings of similar patterns across the north‐east Atlantic Ocean and the Mediterranean Sea. These novel data from the most isolated archipelago of the North Atlantic Ocean, located in a biogeographic boundary area where colonization opportunities are reduced, reinforce the need for long‐term monitoring programmes of coastal fish communities and, in particular, of indicator species groups to improve understanding of the effects of climate change on marine communities.